Study on safety of non-descent vaginal hysterectomy for enlarged uterine size for benign uterine pathologies - Manda, Neelam; Nagar, Oby; Rajoria, Lata; Dadhich, C. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vaginal hysterectomy is less commonly performed for benign pathologies if the uterine size exceeds 12 weeks in the belief that complications could be higher in this group. The aim of this prospective study was to compare surgical outcomes and safety of vaginal hysterectomy in women with non-prolapsed uteri of >12 weeks size to those with uteri of<12 weeks removed vaginally for similar indications. Methods: In this prospective cohort study, 92 patients were included who underwent NDVH for benign uterine conditions between May 2016 to December 2018. The index group comprised 32 women who underwent vaginal hysterectomy for non-prolapse uterus with uterine enlargement (>12 weeks), while the control group consisted of 60 women with uteri <12 weeks. Demographic data, duration of surgery, blood loss, intraoperative and postoperative complications were compared. Results: Women in the two groups had statistically similar mean age, Body Mass Index and parity (44 vs 42.77 years, 20.8 vs 21.56 kg m3 and 3.26 vs 3.83, respectively; p > 0.05). The mean operative time was significantly longer in the index group (62.47min; vs 48.17 min; p <0.0001). Women with enlarged uteri had greater mean estimated blood loss (123.2 ml vs 75.9 ml; p < 0.0001) but the mean length of hospital stay was similar (5.531 days vs 5.177 days; p > 0.05). Intra- and post-operative complications such as blood transfusion and pelvic sepsis, post-operative febrile illness and systemic infections were comparable in both groups. Conclusions: Vaginal hysterectomy in larger non-prolapsed uteri takes longer to perform and is associated with more blood loss compared to uteri <12 weeks but is not associated with a significant increase in complication rates.